2016
DOI: 10.1111/apm.12547
|View full text |Cite
|
Sign up to set email alerts
|

Influence of volatile organic compounds emitted by Pseudomonas and Serratia strains on Agrobacterium tumefaciens biofilms

Abstract: The ability to form biofilms plays an important role in bacteria-host interactions, including plant pathogenicity. In this work, we investigated the action of volatile organic compounds (VOCs) produced by rhizospheric strains of Pseudomonas chlororaphis 449, Pseudomonas fluorescens B-4117, Serratia plymuthica IC1270, as well as Serratia proteamaculans strain 94, isolated from spoiled meat, on biofilms formation by three strains of Agrobacterium tumefaciens which are causative agents of crown-gall disease in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 37 publications
(61 reference statements)
0
20
0
Order By: Relevance
“…) and bacteria biofilms (Plyuta et al. ). VOCs can act as signaling molecules to synchronize certain actions such as sporulation mediated by geosmin (Schöller et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…) and bacteria biofilms (Plyuta et al. ). VOCs can act as signaling molecules to synchronize certain actions such as sporulation mediated by geosmin (Schöller et al.…”
mentioning
confidence: 99%
“…Bacteria can use VOCs to interact with other organisms: bacteria, fungi, plants (Effmert et al 2012, Weise et al 2012, Bos et al 2013, Farag et al 2013, Audrain et al 2015, Giorgio et al 2015. For example, bacterial VOCs differently influence plant growth and productivity (Bailly andWeisskopf 2012, Kanchiswamy et al 2015), suppress the development of different invertebrates, fungi and bacteria (Popova et al 2014), and affect bacterial Quorum sensing systems (Plyuta et al 2014) and bacteria biofilms (Plyuta et al 2016). VOCs can act as signaling molecules to synchronize certain actions such as sporulation mediated by geosmin (Sch€ oller et al 2002) within an organism or a population, or to impact other organisms living in the environment (Stahl andParkin 1976, Bruce et al 2005).…”
mentioning
confidence: 99%
“…In this study, most ketones did not show an inhibition effect on C. fimbriata, except acetone. Ketones produced by Pseudomonas chlororaphis 449 inhibited the formation of biofilms of Agrobacterium tumefaciens and reduced the number of living cells in mature biofilms [52]. Volatile ketones may form Schiff bases with amino groups of proteins, which interferes with the normal functions of proteins [52].…”
Section: Discussionmentioning
confidence: 99%
“…Ketones produced by Pseudomonas chlororaphis 449 inhibited the formation of biofilms of Agrobacterium tumefaciens and reduced the number of living cells in mature biofilms [52]. Volatile ketones may form Schiff bases with amino groups of proteins, which interferes with the normal functions of proteins [52]. Sulfur compounds and terpenoid compounds were not listed in the table because their content was very low.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that ketones bind with protein (bovine serum albumin) [12]. Moreover, 2-nonanone and 2-undecanone demonstrated an inhibitory action on protein refolding in bacteria [13], which can suppress the expression of genes involved in Quorum Sensing regulation in bacterial cells [14] and negatively affected biofilm formation by Agrobacterium tumefaciens [15].…”
Section: Introductionmentioning
confidence: 99%